2008
DOI: 10.1093/bja/aen236
|View full text |Cite
|
Sign up to set email alerts
|

Development and validation of a preoperative scoring system to predict 30 day mortality in patients undergoing hip fracture surgery

Abstract: We have developed and validated a scoring system that reliably predicts the probability of mortality at 30 days for patients after hip fracture.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

14
351
3
2

Year Published

2013
2013
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 304 publications
(370 citation statements)
references
References 24 publications
14
351
3
2
Order By: Relevance
“…Our result of an area under the ROC curve of 0.67 is within the range of 0.64‐0.77 reported in previous studies12, 19, 21, 23, 32 and suggests an equally poor discrimination for POSSUM and the NHFS in our cohort. Interestingly, while some studies have demonstrated superior discrimination by scores specifically designed for hip fracture patients12 compared to that of general surgical risk scores several other studies have not been able to demonstrate such a difference 19, 32. Our results align with the latter studies and illustrate the importance of external validation of risk prediction scores.…”
Section: Discussionsupporting
confidence: 86%
See 3 more Smart Citations
“…Our result of an area under the ROC curve of 0.67 is within the range of 0.64‐0.77 reported in previous studies12, 19, 21, 23, 32 and suggests an equally poor discrimination for POSSUM and the NHFS in our cohort. Interestingly, while some studies have demonstrated superior discrimination by scores specifically designed for hip fracture patients12 compared to that of general surgical risk scores several other studies have not been able to demonstrate such a difference 19, 32. Our results align with the latter studies and illustrate the importance of external validation of risk prediction scores.…”
Section: Discussionsupporting
confidence: 86%
“…The NHFS was developed in response to reports of poor performance of POSSUM in hip fracture patient 9, 19. Our result of an area under the ROC curve of 0.67 is within the range of 0.64‐0.77 reported in previous studies12, 19, 21, 23, 32 and suggests an equally poor discrimination for POSSUM and the NHFS in our cohort.…”
Section: Discussionsupporting
confidence: 74%
See 2 more Smart Citations
“…Predicted mortality after fractured neck of femur fracture nationally is measured at 20–35% 1–3 . The mortality for fractured neck of femur can be measured using previously published scoring systems (eg Nottingham Hip Fracture Score [NHFS]) 4 but these can be cumbersome and sometimes impractical when deciding on patient management. A simpler solution would be to use biochemical markers measured routinely on admission.…”
mentioning
confidence: 99%